1873 Mo. Laws 328 - (:unkn) unknown (My University, 1873)
An Act to Incorporate The Town Of Moberly, art. III, § 1, pt. 15: Any person who shall threaten, quarrel, challenge or fight within said city, or any person who shall be found intoxicated, who shall carry concealed deadly weapons in said city, or any person who shall be found guilty of a misdemeanor, and to define what acts shall constitute a misdemeanor.
Keywords: CARRY - CONCEALED